Oral antibiotics increase blood neutrophil maturation and reduce bacteremia and necrotizing enterocolitis in the immediate postnatal period of preterm pigs. Issue 1 (January 2016) - Nguyen, Duc Ninh; Fuglsang, Eva; Jiang, Pingping; Birck, Malene M; Pan, Xiaoyu; Kamal, Shamrulazhar BS; Pors, Susanne E; Gammelgaard, Pernille L; Nielsen, Dennis S; Thymann, Thomas; Levy, Ofer; Frøkiær, Hanne; et al.
Immature immunity may predispose preterm neonates to infections and necrotizing enterocolitis (NEC). Intravenous antibiotics are frequently given to prevent and treat sepsis, while oral antibiotics are seldom used. We hypothesized that oral antibiotics promote maturation of systemic immunity and delay gut bacterial colonization and thereby protect preterm neonates against both NEC and bacteremia in the immediate postnatal period. Preterm pigs were given formula and administered saline (CON) or broad-spectrum antibiotics orally (ORA) or systemically (SYS) for 5 d after birth. Temporal changes in blood parameters and bacterial composition in the intestine, blood and immune organs were analyzed. Newborn preterm pigs had few blood neutrophils and a high frequency of progenitor cells. Neutrophils gradually matured after preterm birth with increasing CD14 and decreasing CD172a expressions. Preterm neutrophil and monocyte TLR2 expression and TLR2-mediated blood cytokine responses were low relative to adults. ORA pigs showed enhanced blood neutrophil maturation with reduced cell size and CD172a expression. Only ORA pigs, but not SYS pigs, were protected from a high density of gut Gram-positive bacteria, high gut permeability, Gram-positive bacteremia and NEC. Neonatal oral antibiotics may benefit mucosal and systemic immunity via delayed gut colonization and enhanced blood neutrophil maturation just after preterm birth.